On the Trail of Library Projects: Discovering Transformative Power of Cross-sector and Community-driven Partnerships - Vasilije Milnović (21692867) (2025)
This Presentation was given by Dr. Vasilije Milnović. Libraries Lead Forum 2025/The Scientific Center, University Library Belgrade, Serbia (IFLA MENA 2025) Library projects are an excellent platform for reflection and research on strategic partnerships as a dynamic form of intercultural communication and cross-sector collaboration. The interdisciplinary nature of library projects is extremely conducive to international dialogue across sectors and disciplines. University Library Belgrade (UBSM) has extensive project experience and has covered a wide range of topics, from archival and historical materials to capacity building and social engagement. UBSM became influential among Serbian libraries by having various hands-on international collaborations and related journeys. All these had the aim of enhancing skills and knowledge using methods that ignite imagination, creativity and innovative thinking but in relation to solving real-world problems. Of these, the EU-funded projects "Migrants and Local Communities Actively Growing Together for Inclusive Societies" (https://milagroproject.eu/), and "Citizen-Enhanced Open Science in Southeastern Europe Higher Education Knowledge Hubs" (https://ceosse-project.eu/), are particularly striking examples. In some of these projects, the library stepped outside the usual curriculum to tackle social challenges and as a result received extremely high ratings from evaluators. Part of this talk will also be dedicated to the digital context of library work related to international cooperation, as libraries are the entry points to the digital world. The role of libraries is to become an information hub where heritage and culture are embedded in a digital context, increasing visibility and making local heritage global while experimenting with new technologies. This was particularly evident in the project "Distant Reading for European Literary History" (https://www.distant-reading.net/). To support the sustainability of this project and foster international collaboration, a series of smaller initiatives have been developed to explore the role of language and heritage in a digital context. Other Information Presentation was given at: Libraries Thriving Together in an Open Ecosystem https://www.qnl.qa/en/libraries-lead-forum-2025 License: https://creativecommons.org/licenses/by/4.0/ Conference information: Libraries Lead Forum 2025 https://www.qnl.qa/en/libraries-lead-forum-2025/agenda